Exclusion within the inclusion practices of learners with hearing impairment in inclusive schools: A systematic review - Salimini Mbazi; Patrick Ojok; Stackus Okwaput (International Journal of Studies in Inclusive Education)
This systematic review examines the exclusion within the inclusion practices of learners with hearing impairment (LwHI) in inclusive schools. Four databases, Google Scholar, PubMed, EBSCO-host, and Research Gate, were used. The study was guided by the 5W+1H framework for systematic review. The search was conducted in September 2024, and the searching strategies were Boolean operators (AND, OR, and NOT) and proximity operators (SAME and NEAR). The eligibility of the studies was ensured using PRISMA guidelines, and the reviewed studies were appraised using the Critical Appraisal Skills Programme (CASP). The database search identified 108 studies; only 27 were eligible for the study after screening. The reviewed studies were analysed narratively, and no statistical data were presented in the results. Based on the established research questions, it was revealed that the availability and use of hearing assistive devices like hearing aids and cochlea implants, support services from audiologists and speech therapists, use of total communication, use of teaching aids, provision of extra time when teaching LwHI, the low pace of teaching and use of inclusive instructional and assessment strategies are some of the inclusion practices in inclusive schools. In contrast, negative attitudes towards LwHI, use of exclusive instructional and assessment strategies, rigid curriculum, poor seating arrangement, and inadequate skills in sign language are the critical exclusion practices that hinder the inclusion of LwHI in inclusive schools. This review highlights that exclusion practices exist because of the poor preparation of teachers to teach in inclusive schools and poor infrastructures in inclusive schools.